Effect of Time-varying Friction Factors on the Contact Fatigue Life of Gears - Li Xuefei; Li Jiqiang; Chen Zhuo; Li Zhiyuan; Shi Lubing; Liu Zhongming (Jixie chuandong)
The tooth surface friction has an important impact on the tooth surface contact stress and the tooth surface contact fatigue life. In the estimation of the contact fatigue life of the tooth surface, the influence of the friction force of the tooth surface is often ignored, which is not conducive to the accurate prediction of the contact fatigue life of the tooth surface. In order to accurately predict the contact fatigue life of the tooth surface, the R-S-N curves are fitted based on the three-parameter Weibull distribution and the nominal stress method according to the tooth surface contact fatigue test data of 18CrNiMo7-6 gear material. By calculating the contact stress on the tooth surface, the time-varying friction factor is introduced, and the influence of the time-varying friction factor on the contact fatigue life of the tooth surface is analyzed. Finally, the tooth surface contact fatigue test is used to verify the validity. The results show that the contact fatigue limit of tooth surface estimated by the traditional nominal stress method is large due to the influence of the time-varying friction factor, and the influence of the friction factor on contact fatigue life of tooth surfaces decreases with the increase of stress.